The Relationship of Student Learning Discipline and Learning Outcomes in The Indonesian Language Subject Class V of Elementary School - Oktarian, Pira; Amaliyah, Nurrohmatul (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
This research aims to determine the relationship between learning discipline and Indonesian language learning outcomes for class V students at SD Negeri 1 Dendang. This research uses a quantitative approach with a correlation method. The sample was determined using a saturated sample technique or census with 39 students as respondents. Data collection techniques using questionnaires, documentation studies and interviews. To determine the level of relationship between learning discipline and learning outcomes, the Product Moment Correlation formula is used. From the calculation results, the rxy value is 0.923, which means it has a very strong relationship. The results of the hypothesis test obtained a significance value from the Coefficients table of 0.001 <0.05 and a t value of 14,565 > t table 2,026. through this test, it was concluded that learning discipline and Indonesian language learning outcomes had a positive and significant relationship so that hypothesis H1 was accepted, meaning that there was a relationship between student learning discipline and Indonesian language learning outcomes for class V SDN 1 Dendang.